Localized technological externalities and the geographical distribution of firms - Giulio Bottazzi; Pietro Dindo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
Using an analytically solvable equilibrium model, we study how the distribution of economic activities is affected by the trade-off between pecuniary externalities, as dependent on transportation costs, and localized technological externalities, as dependent on inter-regional spillovers. We model localized technological externalities as having a cost saving effect that can be interpreted both as a tangible technological advantage, like the presence of a stronger industrial infrastructure, and as an intangible advantage, like a more efficient labour force composition or the presence of some inter-firms knowledge spillover. Under the assumption of capital mobility and labour immobility, we show that whereas decreasing transportation costs, i.e. promoting market openness, leads to sudden agglomeration, increasing inter-regional spillovers, i.e. promoting technological openness, favors a smoother transition between different levels of firms concentration and ultimately leads to a less uneven distribution of welfare.
Keywords: F12; F15; R12; O3; 330; New Economic Geography; Agglomeration; Footloose capital models; Technological externalities; Market and technological openness; Industriegeographie; Wirtschaftsgeographie; Agglomerationseffekt; Raumwirtschaftstheorie